2021
DOI: 10.3390/ijms222111779
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Analysis of the Dual Inhibition of MG-132 against SARS-CoV-2 Main Protease (Mpro/3CLpro) and Human Cathepsin-L

Abstract: After almost two years from its first evidence, the COVID-19 pandemic continues to afflict people worldwide, highlighting the need for multiple antiviral strategies. SARS-CoV-2 main protease (Mpro/3CLpro) is a recognized promising target for the development of effective drugs. Because single target inhibition might not be sufficient to block SARS-CoV-2 infection and replication, multi enzymatic-based therapies may provide a better strategy. Here we present a structural and biochemical characterization of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 67 publications
2
86
1
Order By: Relevance
“…Biochemical activity of M pro was analyzed using a quenched fluorescent peptide substrate DABCYL-KTSAVLQ↓SGFRKM-EDANS (Bachem; catalog no. 4045664), which has been used in multiple recent studies ( 33 , 34 , 60 ). M pro cleavage between Gln and Ser liberates fluorescence, which was quantified by excitation and emission at 350 and 490 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical activity of M pro was analyzed using a quenched fluorescent peptide substrate DABCYL-KTSAVLQ↓SGFRKM-EDANS (Bachem; catalog no. 4045664), which has been used in multiple recent studies ( 33 , 34 , 60 ). M pro cleavage between Gln and Ser liberates fluorescence, which was quantified by excitation and emission at 350 and 490 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these types of enzymes that work in a proteolytic network are proposed as therapeutic targets to reduce the rate of viral infection. Even in this sense, inhibitors with Cathepsin/Mpro dual activity have been proposed, such as Calpain Inhibitor I and II [ 71 ], which were identified in our virtual screening data ( Figure 5 L, entry L in Table 2 ); recently, the dual activity of the inhibitor M-132 (Cbz-Leu-Leu-Leu-al) was also reported [ 72 ].…”
Section: Resultsmentioning
confidence: 94%
“…Based on the predicted score ranking and availability, we selected 50 molecules for experimental validation and eventually identified 12 compounds with more than 50% inhibition against CTSL activity at 100 μM in a cell-free system, five of which, Mg-132, Z-FA-FMK, Leupeptin Hemisulfate, Mg-101 and Calpeptin, were able to exert inhibition at nanomolar concentrations. It is reported that proteasome inhibitor, Mg-132, can also cross-inhibit CTSL [51] , [52] . Cysteine protease inhibitors, Z-FA-FMK, Leupeptin Hemisulfate, MG-101 and calpain inhibitor, calpeptin were also reported to inhibit CTSL [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] .…”
Section: Discussionmentioning
confidence: 99%